500 tips for tutors - Race, Philip (500 tips series., 2005)
This book contains over 500 practical suggestions designed to help tutors establish active learning amongst their students. Divided into useful sections the tips cover the gamut of teaching and learning situations and comprise a 'start anywhere', dip-in resource suitable for both the newcomer and the old hand. Intended mainly for the university or college lecturer involved in learner-centred learning, the book offers fresh ideas and food for thought on six broad areas of the job:* Getting your students going* Starting off, and working together* The programme itself - lectures, assignments and.